Aranda, Arrernte or Arrarnta? The Politics of Orthography and Identity on the Upper Finke River. Issue 3 (17th November 2017) - Kenny, Anna
Abstract : The Aboriginal people of the Upper Finke River in central Australia have followed a literacy tradition for over 130 years. When the first Lutheran missionaries arrived, they immediately started to study the local Arandic language and were teaching reading and writing by 1879. Despite this long exposure to literacy and the Lutheran influence on it, the issue of the right orthography for this Arandic language variety is emotionally charged and politically very contested. In this post‐colonial context, orthography has become a sociocultural and symbolic, rather than a phonemic, matter.